The functional and stylistic aspect of media speech in media linguistics - Kuralova, Altynkyz T.; Aizhana A. Sholakhova, Elmira K. Yerkebekova; Momynova, Bagdan K.; Utelbayeva, Nurzhigan M. (Opción, 1970)
The study aims to investigate the functional and stylistic aspects of media speech in media linguistics via comparative qualitative research methods. As a result, an important role for the expression of opinion and evaluation in information and analytical texts is played by ideologically-modal vocabulary. In conclusion, the specificity of print media consists of the interaction of verbal and graphic components, radio-in a combination of signs of verbal and sound series.